Characterization of Hit Compounds Identified from High-throughput Screening for their Effect on Blood–brain Barrier Integrity and Amyloid-β Clearance: In Vitro and In Vivo Studies. (21st May 2018) - Elfakhri, Khaled H.; Duong, Quoc-Viet; Langley, Courtney; Depaula, Ashley; Mousa, Youssef M.; Lebeouf, Trista; Cain, Courtney; Kaddoumi, Amal
Graphical abstract: Highlights: The BBB as a therapeutic target against AD is proposed. The developed cell-based BBB model provided a functional predictive in vivo tool to select hit compounds. Drugs that enhance BBB tightness and function have the potential to reduce Aβ pathology associated with AD. α-Tocopherol is a promising compound to prevent, hold or slow the progression of AD. Abstract: In Alzheimer's disease (AD) the blood–brain barrier (BBB) is compromised, thus therapeutic targeting of the BBB to enhance its integrity and function could be a unique approach to treat, slow or hold the progression of AD. Recently, we have developed an in vitro high-throughput screening assay to screen for compounds that increase the integrity of a cell-based BBB model. Results from primary screen identified multiple hit compounds that enhanced the monolayer integrity. Herein, further characterization of selected hit compounds, namely 8-bromoguanosine cyclic monophosphate, JW74, 1, 10-phenanthroline monohydrate, SB216763 and α-tocopherol was performed. Compounds were subjected to concentration-dependent studies to determine their EC50 and potency to enhance the cell-based model integrity by the Lucifer Yellow permeability and amyloid-beta (Aβ) transport across the monolayer. The compounds demonstrated different EC50s to enhance the monolayer integrity ranging from 0.4 to 12.8 µM, and different effect on enhancing Aβ transport with highest transport observed for α-tocopherol (2.2-fold increase). Such effects were associated with increased levels of tight junction proteins such as claudin-5 and/or ZO-1, and Aβ major transport proteins LRP1 and P-glycoprotein. In vivo studies for α-tocopherol were performed in AD mouse model; consistent with the in vitro results α-tocopherol significantly increased BBB integrity measured by IgG extravasation, and reduced brain Aβ levels. In conclusion, findings support our developed cell-based BBB model as a functional predictive in vivo tool to select hit compounds, and suggest that enhancing BBB tightness and function has the potential to reduce Aβ pathology associated with AD.